Nipple adenoma arising from axillary accessory breast: a case report - Shioi, Yoshihiro (BioMed Central, 2012)
Nipple adenoma is a relatively rare benign breast neoplasm, and cases of the disease arising from the axillary accessory breast have very seldom been reported in the English literature. We report a case of nipple adenoma arising from axillary accessory breast including clinical and pathological findings. An 82-year-old woman presented with the complaint of a small painful mass in the right axilla. Physical examination confirmed a well-defined eczematous crusted mass that was 8 mm in size. The diagnosis of nipple adenoma was made from an excisional specimen on the basis of characteristic histological findings. Microscopic structural features included a compact proliferation of small tubules lined by epithelial and myoepithelial cells, and the merging of glandular epithelial cells of the adenoma into squamous epithelial cells in the superficial epidermal layer. Because clinically nipple adenoma may resemble Paget’s disease and pathologically can be misinterpreted as tubular carcinoma, the correct identification of nipple adenoma is an important factor in the differential diagnosis for axillary tumor neoplasms. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1186821489769063